2011
DOI: 10.1177/0165551511420217
|View full text |Cite
|
Sign up to set email alerts
|

Review of James Hartley’s research on structured abstracts

Abstract: Structured abstracts have been employed in biomedical journals for more than 20 years. Professor James Hartley in the School of Psychology, Keele University, UK has published over 25 research papers and conducted systematic studies on structured abstracts. This paper reviews this research from five perspectives: the advantages of structured abstracts over traditional ones, the typographic layout of structured abstracts, the content of structure abstracts, the application of structured abstracts to medical, non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…The preeminent researcher into the efficacy of structured abstracts, James Hartley, reviewed some 31 studies that had been performed by 2004 and found that these studies demonstrated the superiority of structured abstracts. 3 His review, as well as others, 4 showed that structured abstracts…”
Section: What Is a Structured Abstract?mentioning
confidence: 87%
“…The preeminent researcher into the efficacy of structured abstracts, James Hartley, reviewed some 31 studies that had been performed by 2004 and found that these studies demonstrated the superiority of structured abstracts. 3 His review, as well as others, 4 showed that structured abstracts…”
Section: What Is a Structured Abstract?mentioning
confidence: 87%
“…Abstracts of published manuscripts were introduced in the 1950s (Zhang and Liu, 2011). The notion of an abstract is part of everyday language, but its definitions are multiple: the term "abstract" is used loosely to refer to almost any brief account of a longer paper.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, researchers have carried out a number of studies on structured abstracts from different perspectives, and compared abstracts in biomedical journals with those from social sciences journals (see review of James Hartley's research on structured abstracts; Zhang and Liu, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The processes of information representation discussed include abstracting and indexing. As for abstracting, I strongly recommend reference to structured abstracts (Hartley & Betts, ; Zhang & Liu, ). Although it is useful to mention keyword indexing, pre‐ and postcoordinate indexing, citation indexing, the vector model to indexing, and latent semantic analysis, I think it would have added value to the book to very briefly refer the reader to guidelines and standards on indexing as well (similar to what is done for abstracting).…”
mentioning
confidence: 99%